2019
DOI: 10.1186/s41044-018-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating associative classification algorithms for Big Data

Abstract: Background: Associative Classification, a combination of two important and different fields (classification and association rule mining), aims at building accurate and interpretable classifiers by means of association rules. A major problem in this field is that existing proposals do not scale well when Big Data are considered. In this regard, the aim of this work is to propose adaptations of well-known associative classification algorithms (CBA and CPAR) by considering different Big Data platforms (Spark and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…During this step, the predictive power of the classifier is measured using prediction accuracy or error rate. In the last decade, multiple research studies, for example [4], [7] have reported the applicability of AC on various different applications including fraud detection, credit card scoring, bioinformatics, on-line security, medical diagnoses, text categorization and others. The wide spread of this classification approach is primarily due to the simplicity and interpretability of the rules in the classifier besides the high predictive accuracy of its classifiers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…During this step, the predictive power of the classifier is measured using prediction accuracy or error rate. In the last decade, multiple research studies, for example [4], [7] have reported the applicability of AC on various different applications including fraud detection, credit card scoring, bioinformatics, on-line security, medical diagnoses, text categorization and others. The wide spread of this classification approach is primarily due to the simplicity and interpretability of the rules in the classifier besides the high predictive accuracy of its classifiers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Any potential rule that was unable to classify at least one training example is discarded. A number of successive AC algorithms have adopted the CBA database coverage method like CBA (2) [10] and ACCF [11], (uCBA) [12], X-class [13], SPARK-CBA [7], and others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…DM contains a rich set of classification models; specifically, Support Vector Machine [9], Rule Based [10], Decision Tree [11,12], Bayesian classification [2], k -Nearest Neighbor [13], and AC [14]. Among all, AC is relatively new and promising [15,16,17,18,19,20,21,22,23,24] as it combines the best approaches of association rules mining (ARM) and classification. AC is based on ARM where, first, the strongest Class Association Rules (CAR) are discovered from dataset, followed by converting those rules into classifier model.…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of AC in 1997, numbers of algorithms are developed in this family e.g. CBA [14,25], CMAR [18], CPAR [21], MCAR [19], MAC [26], CMARAA [27], MRAC & MRAC+ [15], DAC [23], CBA-Spark and CPAR-Spark [24] and G3P-ACBD [28]. Almost all consist of three basic steps -a) Association rule generation, b) Classifier building -rule pruning and rule ranking c) Classification of unknown records using the classifier.…”
Section: Introductionmentioning
confidence: 99%